The Pathophysiology of Degenerative Cervical Myelopathy and the Physiology of Recovery Following Decompression - Akter, Farhana; Yu, Xinming; Qin, Xingping; Yao, Shun; Nikrouz, Parisa; Syed, Yasir Ahmed; Kotter, Mark (Frontiers in Neuroscience, 2020)
Background: Degenerative cervical myelopathy (DCM) is the most common cause of spinal cord compression in adults. The mainstay of treatment is surgical decompression. Surgery can halt disease progression and enable a degree of recovery; however, outcomes remain poor. A better understanding of the pathogenesis is required for the development of treatments to improve outcomes following surgery. Objective: To systematically evaluate the pathophysiology of DCM. Methods: A total of 13,806 published articles were identified in our systematic search of electronic databases (PUBMED, WEB OF SCIENCE). A total of forty-nine studies investigating the secondary injury mechanisms of DCM or physiology of recovery in animal models of disease underwent comprehensive review. Results: Forty-six papers addressed the pathophysiology of DCM. There is evidence of neuronal loss and supporting cells following compression. A number of studies provided some evidence of myelin change, however whether this translated to demyelination is not fully known. There was evidence of cell apoptosis and increased inflammation following compression in a number of studies. Only three papers investigated the decompressed spinal cord. These included one study demonstrating axonal plasticity following decompressive surgery. However, another study demonstrated ischaemic-reperfusion injury following decompression, which may be detrimental to recovery. Conclusions: In preclinical studies, the pathophysiology of DCM has been poorly studied and a number of questions remain unanswered. The physiological changes seen in the decompressed spinal cord has not been widely investigated and it is paramount that researchers investigate this further to enable the development of therapeutic tools, which can enhance recovery following surgery.